Reconciling Performance and Ethics: A Critical Analysis of Modern AI Image Generation Systems - Satya Krishna Kapil Tadikonda, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the complex interplay between technical advancements and ethical considerations in contemporary AI-driven image-generation systems. The article analyzes recent breakthroughs in deep learning architectures and generative adversarial networks that have dramatically improved image fidelity, resolution, and personalization capabilities. The technical discussion focuses on performance optimization techniques, including strategies for reducing inference latency and enhancing model efficiency across diverse computational environments. Concurrently, the article addresses critical ethical dimensions, including algorithmic bias, content authenticity challenges, and implications for digital identity. The article further explores industry transformations across digital marketing, entertainment, and social media while evaluating emerging safeguards such as AI watermarking and detection technologies. Through a multidisciplinary lens, the article proposes that sustainable advancement in AI image generation requires balanced consideration of both technical innovation and ethical governance frameworks, with particular attention to regulatory approaches that can adapt to this rapidly evolving technological landscape.
Keywords: Deep learning; Generative adversarial networks; Inference optimization; Algorithmic bias; Digital authenticity